A study of the depth and size of concave cube Au nanoparticles as highly sensitive SERS probes. Issue 13 (16th March 2016) - Romo-Herrera, J. M.; González, A. L.; Guerrini, L.; Castiello, F. R.; Alonso-Nuñez, G.; Contreras, O. E.; Alvarez-Puebla, R. A.
Abstract : High and uniform near fields are localized at the eight similar sharp corners of cubic gold nanoparticles. Moreover, by introducing concavity such fields can be further increased and tuned in the near infrared region. Abstract : High and uniform near fields are localized at the eight similar sharp corners of cubic gold nanoparticles. Moreover, by introducing concavity in the particle lateral planes, such field intensities can be further increased and tuned in the near infrared region without altering the overall size of the nanoparticles. Herein, we perform a thorough investigation of the morphological, crystallographic and plasmonic properties of concave gold nanocubes (GNCs) in the sub-70 nm size range, for their potential application as highly efficient SERS substrates in size-limiting cases. Theoretical calculations indicate that the highest increment of the near-field is located at the eight sharp tips and, interestingly, a medium near-field increment is also activated over the volume next to the concave surface. Remarkably, the plasmonic response of the concave cubic morphology showed great sensitivity to the concavity degree. Experimental SERS analysis nicely matches the outcome of the theoretical model, confirming that medium-sized concave GNCs (35 nm side length) possess the highest SERS activity upon excitation with a 633 nm laser, whereas larger 61 nm side concave GNCs dominate the optical response at 785 nm. Due to their size-intensity trade off, we envision that such small concave gold nanocubes can provide a highly active and efficient SERS platform for size-limiting applications, especially when near infrared excitations are required.